The underlying mechanisms of the effect of superchilling on the tenderness of beef Longissimus lumborum. (December 2022) - Chen, Xue; Luo, Xin; Zhu, Lixian; Liang, Rongrong; Dong, Pengcheng; Yang, Xiaoyin; Niu, Lebao; Hopkins, David L.; Gao, Shujuan; Mao, Yanwei; Zhang, Yimin
Abstract: This study investigated the effect of superchilling (−30 °C until the core temperature achieved −3 °C, then stored at −1 °C until 24 h, SC) on the tenderness of hot boned beef M. longissimus lumborum (LL), with very fast chilling (−30 °C until the core temperature achieved 0 °C, then stored at −1 °C until 24 h, VFC) and conventional chilling (0– 4 °C for 24 h, CC) as the controls. The lowest initial shear force values were obtained in SC samples compared to those from the VFC and CC treatments ( P < 0.05). Clear freezing damage of muscle fibers and more myofibril fragmentation were found in SC samples compared with the other samples early post-mortem. Moreover, SC samples showed the highest level of inosine 5-monophosphate at 3 h post-mortem ( P < 0.05). A reduced glycolysis rate (as evidenced by lactate content) was also found in SC treated samples suggesting little contribution of glycolysis on the tenderization of SC. Highlights: Superchilling (SC) can improve beef tenderness. SC caused greater desmin and troponin-T degradation at 7 and 14 days of ageing. SC caused obvious freezing damage of muscle fibers and more myofibril fragmentation. The higher level of IMP in SC treatment may weaken the actin-myosin bridge. SC did not affect the levels of glycolysis enzymes but reduced the glycolysis rate.